The Vulnerability-Stress-Model—Holding Up the Construct of the Faulty Individual in the Light of Challenges to the Medical Model of Mental Distress - Demke, Elena (Frontiers in Sociology, 2022)
In the late 1970s, the course seemed to be set for a reconciliation of the controversy around the somatic vs. the social nature of mental distress. The biopsychosocial model and the vulnerability-stress-model were influential agents in this move, but a medicalized somatic view on mental distress persisted nonetheless. The reasons for this persistence are complex, and naturally include questions of structural power. However, the adherence to a certain fundamental framing of a problem may continue to be transmitted not only out of conviction, but also unwittingly. The vulnerability-stress-model allowed those who used it to effectively stick to the implications of a medicalized somatic view of the faulty individual who falls ill, while also allowing them to believe they integrated the social dimensions of the problem. A close reading and hermeneutical interpretation of the text by Zubin and Spring (1977) and an analysis of its use in psychoeducation serve as a case study in this respect. The vulnerability-stress-model (simply called “vulnerability model” by Zubin and Spring; more often “stress-vulnerability model” by English speaking recipients, and “vulnerability-stress-model” by German authors) seems to have been a success story: since its publication by Zubin and Spring (1977), it has been the point of reference for numerous scholarly and popular (“psychoeducational”) adaptations. It was soon extended from the diagnosis of schizophrenia to various psychiatric diagnoses, understanding mental distress as the result of a trait/state-interaction in the shape of “deviant coping patterns” (Zubin and Spring, p. 112). Recipients appraised the integration of environmental and dispositional factors, some of them opposing the supposed originally integrative intention of the VSM to reduced applications of it (Schmidt, 2012). However, it can be argued that this integration is a matter of rhetorics rather than argumentative essence. Their argument which significantly depends on the use of metaphors, as well as their referencing amounts to a confirmation of a medicalized view on mental distress and a dismissal of the role played by societal factors. Applied to psychoeducation, this paradoxical combination reinforced a view of the persons in question as individually vulnerable, rather than socially wounded. The consequences in terms of what appears as remedy are significant and contribute to turning individual difference into disability.